Structural design and analysis of a passive DMFC supplied with concentrated methanol solution. (1st June 2017) - Fang, Shuo; Zhang, Yufeng; Zou, Yuezhang; Sang, Shengtian; Liu, Xiaowei
Abstract: This paper develops a passive direct methanol fuel cell (DMFC) structure employing the graphite plate as the porous medium in order to increase the energy density and the stable operating time of the cell. A two-dimensional model of the proposed DMFC is developed to determine the appropriate thickness of the graphite plate and the optimum feed concentration of the methanol. The simulated polarization curves and current-power profiles of the model are verified experimentally. Both the modeling results and the experimental results show that the 500 μm thick graphite plate cannot transfer enough methanol to the anode. The simulated and experimental results both illuminate that the DMFC with 300 μm thick graphite plate supplied with 10 M methanol and the one with 400 μm thick graphite plate supplied with 15 M methanol can achieve a normal performance. The energy density of the proposed DMFC is also analyzed by discharging at constant current experimentally. The DMFC with 400 μm thick graphite plate supplied with 15 M methanol has the longest discharging time. The proposed passive DMFC structure significantly improves the energy density and electrical efficiency of the cell. Highlights: A DMFC supplied with high concentration methanol solution is developed. The graphite plate is employed as the porous medium at the anode. A two-dimensional, multi-physics model of the DMFC is established. The experimental results correlate well with the simulation.